Informal caregiving following stroke: a qualitative exploration of carer self-identification, care-related language and support experiences - Richard Brown; Audrey Bowen; Bethany Harcourt (BMJ Open)
Objectives Following a stroke, people often receive informal care from friends and family. Some carers adopt the role quickly, whereas others find it more difficult to see themselves as a ‘carer’ and do not access relevant support. To understand the process of how and when informal carers start to see themselves as such, and their preferred terminology and experiences of support in this role.Design The study adopted an exploratory qualitative design, collecting data through semistructured interviews with participants and a brief survey of participant demographics. Data were analysed thematically using a template analysis approach. Patient, carer and public involvement collaboration, through a formed carer advisory group, enhanced the study methodology.Setting The project was a nationwide study, with participants residing across the UK. The study took place from September 2021 to April 2024.Participants 18 adults (aged 18 years and above) who had provided care or support to a friend or family member after a stroke that occurred at least 1 year prior to participation completed the study.Results Five main themes were developed: (1) adopting and adjusting to the care role, (2) accessibility of support, (3) perceptions of support, (4) acceptability of care-related language and terminology and (5) function of care-related language and terminology. Facilitators and barriers to participants self-identifying with the care role were identified. Self-identification was found to commonly occur at four key points along the stroke trajectory: instant recognition at the time of the stroke event; at the point of planning discharge from hospital; on initial return home from hospital; and at a later stage in the caregiving experience. Two main contrasting opinions around the acceptability of care-related terminology were shared: a favourable view of care-related language and a depreciative view. Accessibility of support services and suggestions for future support provision were discussed.Conclusions Individuals identify as ‘carers’ at different points and to different extents throughout the stroke trajectory. Findings outline the factors that facilitate this self-identification process and those which constitute challenges to adjusting to the role. Recommendations are made relating to the accessibility of support for informal carers of stroke survivors, including: use of more accessible and inclusive care-related language, educational needs relating to what a ‘carer’ is and involvement of carers and wider family in the rehabilitation process.